The Regulatory Mechanism of 2-Acetyl-1-Pyrroline Biosynthesis in Fragrant Rice (Oryza sativa L.) Under Different Soil Moisture Contents - Luo, Haowen; Duan, Meiyang; Kong, Leilei; He, Longxin; Chen, Yulin; Wang, Zhimin; Tang, Xiangru (Frontiers in Plant Science, 2021)
2-acetyl-1-pyrroline (2-AP) is the key compound of rice aroma. However, the responses of 2-AP biosynthesis in fragrant rice under different soil moisture and the corresponding mechanism are little known. The present study evaluated the effects of different soil moisture on 2-AP biosynthesis through a pot experiment. Four soil moisture contents, i.e., 50% (SM50), 40% (SM40), 30% (SM30), and 20% (SM20), were adopted, and SM50 treatment was taken as control. The pots were weighed and watered to maintain the corresponding soil moisture content. The results showed no significant difference in growth parameters (plant height, stem diameter, and plant dry weight) among all treatments. Compared with SM50, SM40, SM30, and SM20 treatments significantly (P < 0.05) increased 2-AP content by 32.81%, 23.18%, and 53.12%, respectively. Between 20 to 90% higher proline content was observed in SM40, SM30, and SM20 treatments than in SM50. Enzymes including proline dehydrogenase, ornithine transaminase, and 1-pyrroline-5-carboxylate synthetase exhibited lower activities with soil moisture declined. Higher diamine oxidase activity was observed in SM40, SM30, and SM20 treatments compared with SM50, and real-time PCR analyses showed that transcript level of DAO1 was greatly increased under low soil moisture treatments, especially in SM20 treatment. Transcript levels of PRODH, DAO2, DAO4, DAO5, OAT, P5CS1, and P5CS2 decreased or maintained in SM40, SM30, and SM20 treatments compared with SM50. We deduced that low soil moisture content enhanced 2-AP biosynthesis mainly by up-regulating the expression of DAO1 to promote the conversion from putrescine to 2-AP. Keywords: Fragrant rice; 2-acetyl-1-pyrroline; gene expression; enzymes; proline; soil moisture